Formation Of Nanotubular Oxide By Anodization Of Valve Metals - Ismail, Syahriza (2013)
The formation of TiO2 nanotubes (TNTs), ZrO2 nanotubes (ZNTs) and segmented WO3 nanotubes (WNTs) by anodization of Ti, Zr, and W metal was successful in fluorinated aqueous and organic electrolyte. In aqueous electrolyte, acidic 1 M Na2SO4 (pH 3). Glycerol and ethylene glycol were the organic electrolyte with their neutral pH. The properties including morphology and structural of the nanotubular oxide formed were investigated. During anodization, the main factors effecting nanotubular structures are types of electrolyte, its composition, anodization voltage applied to anode and anodization time. It was found that TNTs and ZNTs can be formed in both aqueous and organic electrolytes. However WNTs can only be formed in aqueous electrolyte. The morphology of WNTs also different such that they are not really nanotubular but in a form of segmented porous structure. Both ZNTs and TNTs are highly ordered, well aligned and grow perpendicular to the metal foil. The TNTs formed, had the average diameter ranging from 50-100 nm and length of 700 nm. Detailed analysis of annealing on TNTs reveals that, phase formation to anatase occurred at 350oC at 450oC transformation happened. At temperature > 600oC rutile phase dominated. The mechanism of ZNTs formation is found to be based on three dominating process at the early stage of anodization; anodic ZrO2 formation, pits formation, pore formation followed by pore separation process to form nanotubes. The morphologies of ZNTs can be further classified as double layer, single layer, bundled and precipitates on ZNTs.